Effect of Recording Duration on the Diagnostic Performance of Multifocal Visual-evoked Potentials in High-risk Ocular Hypertension and Early Glaucoma - Fortune, Brad (2008)
PURPOSE: To evaluate the effect on diagnostic performance of reducing multifocal visual-evoked potential (mfVEP) recording duration from 16 to 8 minutes per eye. METHODS: Both eyes of 185 individuals with high-risk ocular hypertension or early glaucoma were studied. Two 8-minute mfVEP recordings were obtained for each eye in an ABBA order using VERIS. The first recording for each eye was compared against single run (1-Run) mfVEP normative data; the average of both recordings for each eye was compared against 2-Run normative data. Visual fields (VFs) were obtained by standard automated perimetry (SAP) within 22.3±27.0 days of the mfVEP. Stereo disc photographs and Heidelberg Retina Tomograph images were obtained together, within 24.8±50.4 days of the mfVEP and 33.1±62.9 days of SAP. Masked experts graded disc photographs as either glaucomatous optic neuropathy or normal. The overall Moorfields Regression Analysis result from the Heidelberg Retina Tomograph was used as a separate diagnostic classification. Thus, 4 diagnostic standards were applied in total, 2 based on optic disc structure alone and 2 others based on disc structure and SAP. RESULTS: Agreement between the 1-Run and 2-Run mfVEP was 90%. Diagnostic performance of the 1-Run mfVEP was similar to that of the 2-Run mfVEP for all 4 diagnostic standards. Sensitivity was slightly higher for the 2-Run mfVEP, whereas specificity was slightly higher for the 1-Run mfVEP. CONCLUSIONS: If higher sensitivity is sought, the 2-Run mfVEP will provide better discrimination between groups of eyes with relatively high signal-to-noise ratio (eg, early glaucoma or high-risk suspects). But if higher specificity is a more important goal, the 1-Run mfVEP provides adequate sensitivity and requires only half the test time. Considered alongside prior studies, the present results suggest that the 1-Run mfVEP is an efficient way to confirm (or refute) the extent of VF loss in patients with moderate or advanced glaucoma, particularly in those with unreliable VFs, including malingering or other “functional” forms of VF loss.